Combined Immunoscore of CD103 and CD3 Identifies Long-Term Survivors in High-Grade Serous Ovarian Cancer. Issue 4 (May 2016) - Bösmüller, Hans-Christian; Wagner, Philipp; Peper, Janet Kerstin; Schuster, Heiko; Pham, Deborah Lam; Greif, Karen; Beschorner, Christine; Rammensee, Hans-Georg; Stevanović, Stefan; Fend, Falko; Staebler, Annette
Abstract : Objective: Increased numbers of tumor-infiltrating lymphocytes (TILs) in high-grade serous ovarian cancer (HGSC) are associated with improved clinical outcome. Intraepithelial localization of TILs might be regulated by specific homing receptors, such as CD103, which is widely expressed by intraepithelial lymphocytes. Given the emerging role of CD103 + TILs, we aimed to assess their contribution to the prognostic value of immunoscoring in HGSC. Methods: The density of intratumoral CD3 + and CD103 + lymphocytes was examined by immunohistochemistry on a tissue microarray of a series of 135 patients with advanced HGSC and correlated with CD4 +, CD8 +, CD56 +, FoxP3 +, and TCRγ + T-cell counts, as well as E-cadherin staining and conventional prognostic parameters and clinical outcome. Results: Both the presence of CD103 + cells, as well as high numbers of intraepithelial CD3 + lymphocytes (CD3E), showed a significant correlation with overall survival, in the complete series, as well as in patients with optimal debulking and/or platinum sensitivity. Combining CD3 and CD103 counts improved prognostication and identified 3 major subgroups with respect to overall survival. The most pronounced effect was demonstrated for patients with optimally resected and platinum-sensitive tumors. Patients with CD3 high /CD103 high tumors showed a 5-year survival rate at 90%, CD3 low /CD103 high at 63%, and CD3 low /CD103 low at 0% ( P < 0.001). Conclusions: These results suggest that combined assessment of CD103 and CD3 counts improves the prognostic value of TIL counts in HGSC and might identify patients with early relapse or long-term survival based on the type and extent of the immune response.